2012
DOI: 10.1007/s11661-012-1217-2
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and Hardening in Magnesium Alloys

Abstract: Magnesium alloys have received an increasing interest in the past 12 years for potential applications in the automotive, aircraft, aerospace, and electronic industries. Many of these alloys are strong because of solid-state precipitates that are produced by an age-hardening process. Although some strength improvements of existing magnesium alloys have been made and some novel alloys with improved strength have been developed, the strength level that has been achieved so far is still substantially lower than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
519
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,355 publications
(600 citation statements)
references
References 218 publications
27
519
1
1
Order By: Relevance
“…The results shown in Figure 8 indicated that α-Mg was the major phase, and that the precipitated phases of the as-cast, T4 and T6 samples both contain Mg 24 (Y, Nd) 5 and Mg 3 (Y, Nd); this findings is consistent with Nie's results [13,33]. "Undissolved particles" remained after the solidification process, as shown in Figure 3.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The results shown in Figure 8 indicated that α-Mg was the major phase, and that the precipitated phases of the as-cast, T4 and T6 samples both contain Mg 24 (Y, Nd) 5 and Mg 3 (Y, Nd); this findings is consistent with Nie's results [13,33]. "Undissolved particles" remained after the solidification process, as shown in Figure 3.…”
Section: Resultssupporting
confidence: 85%
“…Various precipitations (e.g., Mg 3 Nd, Mg 12 YNd, Mg 3 (Y, Nd), etc.) may form in a Mg-Y-Nd system [13]. The majority of previous studies have focused on the relationship between precipitations and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the basal precipitates are proposed to have a hexagonal structure with a = 0.556 nm. It is well known that precipitation strengthening is an effective way to strengthen Mg alloy, however, many investigations about precipitation focus on the static precipitation, especially Mg-RE alloys [15,18,26,27]. As mentioned by Kabir [22], the formation of strain-induced precipitates depended on deformation temperature, strain, and strain rate.…”
Section: Microstructures Of As-extruded Alloysmentioning
confidence: 99%
“…These results indicate that it is possible to enhance the mechanical properties of the age-hardened Mg-Sc alloy by controlling the initial microstructure. Figure 6 shows the relationship between the UTS and ultimate tensile elongation in various precipitation-strengthened magnesium alloys with an ultimate tensile elongation of over 5%, where those magnesium alloys were categorized by their production processes into casting, extrusion, equal channel angular pressing (ECAP) and rolling 17,18) . The present age-hardened Mg-Sc alloys show mechanical properties comparable to those of reported high strength magnesium al- loys.…”
Section: Tensile Propertiesmentioning
confidence: 99%